Antioxidants restore protoporphyrinogen oxidase in variegate porphyria patients. (20th April 2013) - Ferrer, Miguel D.; Tauler, Pedro; Sureda, Antoni; Palacín, Clara; Tur, Josep A.; Pons, Antoni
Abstract Background Variegate porphyria (VP) is the result of decreased protoporphyrinogen oxidase (PPOX) activity and results in the accumulation of porphyrins and porphyrin precursors. Our aims were to analyse the basal antioxidant defences and oxidative damage markers and the effects of a diet supplementation with vitamins E and C on the oxidant/antioxidant status and PPOX gene expression in lymphocytes of variegate porphyria (VP) patients. Materials and methods Twelve women affected by VP and 12 control women participated in a randomized and double‐blind crossover study. Each participant took either 50 mg/day vitamin E and 150 mg/day vitamin C or a placebo for 6 months. Results Lymphocyte PPOX gene expression, together with catalase and glutathione peroxidase activities, was reduced in VP women. No differences were observed in the levels of malondialdehyde and protein carbonyl derivatives. Stimulated lymphocyte H2O2 production was higher in porphyric women. Supplementation with antioxidant vitamins increased PPOX expression in VP patients. Glutathione reductase (GRd) and superoxide dismutase (SOD) activities were higher in the treatment groups. Conclusions Lymphocytes from VP patients show reduced PPOX expression and present a greater susceptibility to producing H2O2 and impaired H2O2 detoxifying mechanisms. Supplementation with vitamins E and C restores PPOX expression in VP patients and enhances GRd and SOD activity, suggesting the potential benefits of a diet rich in vitamins E and C in these patients.